Gallegos en Madrid: actitudes y mantenimiento de la Lengua Gallega - Villamil Touriño, Asunción (Madrygal. Revista de Estudios Gallegos, 2004)
This is a sociolinguistic analysis of Galician bilingual inmigrant's attitudes towards Galician and Spanish in Madrid, as well as of the maintenance of the language in the second generation of immigrants. Their attitudes are compared to those of Galician people in Galicia and other bilingual communities and some possible reasons for these attitudes. Sociolinguist, bilingualism, attitudes.